Choices: Making an art of everyday life : Marina Abramovic and Ulay - James Lee Byars - Spalding Gray - Alex Grey - Tehching Hsieh - Linda Montano - Morgan O'Hara - Michael Osterhout - Unted Art Contractors - Ian Wilson - Tucker, Marcia (New York : The New Museum of Contemporary Art, 1986)
Marina Abramovic and Ulay - James Lee Byars - Spalding Gray - Alex Grey - Tehching Hsieh - Linda Montano - Morgan O'Hara - Michael Osterhout - Unted Art Contractors - Ian Wilson
Choices: Making an art of everyday life : Marina Abramovic and Ulay - James Lee Byars - Spalding Gray - Alex Grey - Tehching Hsieh - Linda Montano - Morgan O'Hara - Michael Osterhout - Unted Art Contractors - Ian Wilson, The New Museum of Contemporary Art, New York, February 1 - March 30, 1986
boek